THE ROLE OF ENGLISH IN MODERN PRESCHOOL EDUCATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This annotation explores the role of English in modern preschool education, emphasizing its importance in early childhood development. It highlights how introducing English at an early age improves children’s cognitive abilities, linguistic awareness, communication skills, and cultural understanding. The annotation also discusses effective pedagogical methods such as play-based learning, songs, storytelling, and interactive activities that help preschoolers acquire English naturally. Furthermore, it outlines the benefits of creating an engaging language environment and the role of teachers and parents in supporting early language learning.